Documenting Pornography Use in America: A Comparative Analysis of Methodological Approaches. Issue 7 (1st September 2016) - Regnerus, Mark; Gordon, David; Price, Joseph
Abstract : Estimates of pornography use in the United States range widely. We explore the reasons for the variation in such estimates among U.S. adults using data from four different recent nationally representative samples—each of which asked a different type of question about pornography use. We attribute the notable variation in estimates to differences in question wording and answer options, and assert that a survey question asking respondents about their most recent use of pornography minimizes recall bias and is better poised to assess the overall prevalence of pornography in a population than is the more common approach of asking respondents about their historical general-use pattern. When we privileged the most-recent-use approach, survey data from 2014 reveal that 46% of men and 16% of women between the ages of 18 and 39 intentionally viewed pornography in a given week. These numbers are notably higher than most previous population estimates employing different types of questions. The results have ramifications for methods of surveying sensitive self-reported behaviors and for contextualizing scholars' claims as well as popular conversations about the reach and implications of pornography use in the United States.